Pengetahuan Penggunaan Alat Pelindung Diri Di Meubel Aluminium UD La Tahzan Kabupaten Hulu Sungai Utara - Bella Amellia; Gunung Setiadi; Arifin Arifin (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: Knowledge of the Use of Personal Protective Equipment in UD La Tahzan Aluminum Furniture in Hulu Sungai Utara Regency. The results of the preliminary survey showed that there were 50% of 10 aluminum furniture workers who knew the importance of the benefits and uses of personal protective equipment and 50% knew less. The purpose of this study was to determine the relationship of knowledge with the use of personal protective equipment at UD La Tahzan aluminum furniture in Hulu Sungai Utara Regency. The research method used was an analytical survey with a cross sectional approach. The population in this study amounted to 35 people. Data analysis using X2 (Chi square) test.The results of the study showed that there were 24 people who had poor knowledge there were 23 people who did not use personal protective equipment. Statistical test results (p = 0.007) means that there is a relationship of knowledge with the use of personal protective equipment at UD La Tahzan aluminum furniture in Hulu Sungai Utara Regency. Suggestions for future researchers to measure lighting, noise especially the work climate because it is one of the factors that might influence the use of personal protective equipment.